A panel data analysis on the institutional determinants of foreign direct investment inflows: commonalities between India and China. Issue 3 (11th March 2020) - Gupta, Priya
Developing as well as developed countries seek to attract Foreign Direct Investment (FDI) due to its multiple advantages for economic development. Several studies have been conducted to find out the economic determinants affecting the FDI inflows across the world but not much has been explored on the institutional factors affecting FDI inflows in emerging economies. Therefore, this paper aims to determine whether institutional quality has any significant impact on the FDI inflows in the specific context of India and China using panel data analysis. Under this technique, all the three regression models, i.e., pooled ordinary least square, fixed effects, and random effects are tested to explore the institutional determinants impacting FDI inflows. The empirical results of the modified random effect model reveal that the country's risk rating on corruption and gender parity index are the two most significant institutional determinants impacting the FDI inflows in both India and China commonly.